The effect of game based learning with math bingo in reducing math anxiety to improve students’ mathematics learning outcomes in data presentation materials - Ayyasy, Hafidz Yahya; Asrul, Asrul (Desimal: Jurnal Matematika, 2024)
This study aims to examine the effects of game-based learning with Math Bingo in reducing math anxiety and improving student learning outcomes. The research method used is pre-experimental with a pre-post test design of one group. Math anxiety data was collected using questionnaires before and after the intervention, while math learning outcomes data were obtained through pre-test and post-test. results of data analysis obtained sig. (2-tailed) of 0.001<0.05. Therefore, it can be concluded that game-based learning with Math Bingo is effective in reducing anxiety and improving students' math learning outcomes. This finding shows that game-based learning with Math Bingo is effective in reducing anxiety and improving students' math learning outcomes. The implication of this study is the importance of integrating game-based learning in mathematics learning to create a more interactive and interesting learning environment, as well as the need for support from curriculum developers and educational policies for the wider implementation of this method.